Lower Extremity Kinematics of the Y-Balance Test in Healthy and ACL Injured Adolescent Females - Alison Bulow; Alixandra Bellemare; Judy E Anderson; Jeff R S Leiter; Peter B MacDonald; Jason D Peeler (North American Sports Medicine Institute, 2021)
# Background Adolescent females are at significant risk for sustaining an ACL injury. The Y-Balance Test (YBT) is frequently used to evaluate neuromuscular control and lower extremity function. However, few studies have quantified 2D lower extremity kinematics during performance of the YBT, and there is an absence of kinematic data specific to at-risk adolescent females. # Purpose To examine lower extremity joint kinematics during execution of the YBT by healthy and ACL-injured adolescent females. # Study Design Prospective cohort. # Methods Twenty-five healthy and ten ACL-injured (mean time from injury 143 days) adolescent females were assessed using the YBT. Sagittal and frontal plane knee and ankle motion was video recorded during execution of the YBT anterior reach movement. Ankle dorsi-flexion, knee flexion, and knee valgus angles were quantified via kinematic analysis. ANOVAs with a post hoc Bonferroni correction were used to compare YBT scoring (%LL) and kinematic data between groups. Pearson product-moment correlations determined the relationship between kinematic data and YBT scoring. # Results Healthy and ACL-injured subjects demonstrated similar YBT scores and lower extremity kinematic data. Healthy subjects demonstrated a weak positive correlation between ankle dorsiflexion and YBT scoring, and a weak negative correlation between knee valgus and YBT scoring. These relationships did not exist for ACL-injured subjects. Kinematic data for both groups also demonstrated a large degree of variability, regardless of YBT score. # Conclusions Adolescent females frequently utilize a variety of lower extremity movement strategies when performing a functional movement task, and scoring on the YBT offers limited insight regarding lower extremity joint kinematics and ACL-injury risk in a physically active adolescent female population. # Level of Evidence Level 3.